2016
DOI: 10.1097/mph.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Hypereosinophilic Syndrome: Hacettepe Experience

Abstract: The aim was to evaluate baseline demographic, clinical, and laboratory characteristics, treatment modalities, and outcome of children with idiopathic hypereosinophilic syndrome (HES) followed up in our center. Children who fulfilled the criteria of idiopathic HES followed up at Hacettepe University Faculty of Medicine, Pediatric Hematology Department between June 2004 and October 2013 were included in this study. Medical records of all children with idiopathic HES were reviewed to obtain regarding data. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…After removing duplicate and redundant articles, 25 papers were included in the present study for the final review and analysis. A thorough reading of these articles yielded a total of 32 cases of idiopathic HES with cutaneous involvement 5–29. A comprehensive review of these case reports indicated a slight male predominance (male, n = 19; female, n = 13).…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicate and redundant articles, 25 papers were included in the present study for the final review and analysis. A thorough reading of these articles yielded a total of 32 cases of idiopathic HES with cutaneous involvement 5–29. A comprehensive review of these case reports indicated a slight male predominance (male, n = 19; female, n = 13).…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic HES is rare in children and a limited number of cases have been reported ( 55 57 ). The true incidence is unknown and data on the efficacy of treatment regarding the response and survival of patients is also insufficient ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic HES is rare in children and a limited number of cases have been reported ( 55 57 ). The true incidence is unknown and data on the efficacy of treatment regarding the response and survival of patients is also insufficient ( 55 ). Pediatric HES has been reported to have a slight male prevalence ( 56 ), though a recent study by Williams et al ( 57 ) observed that the female/male occurrence ratio was increased to 23/9 ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Pulmonary involvements during childhood vary from 27.5% to 55.3%. 7 , 9 In the study conducted by Tavil et al 2 half of the pediatric patients had pulmonary involvement presented as cyanosis, crackles on auscultation, and thorax CT findings. 2 In the presented case, the patient had only dry cough and respiratory distress.…”
Section: Discussionmentioning
confidence: 98%